2018
DOI: 10.3847/2041-8213/aaa2f6
|View full text |Cite
|
Sign up to set email alerts
|

GRB 170817A Associated with GW170817: Multi-frequency Observations and Modeling of Prompt Gamma-Ray Emission

Abstract: We present our observations of electromagnetic transients associated with GW170817/GRB 170817A using optical telescopes of Chilescope observatory and Big Scanning Antenna (BSA) of Pushchino Radio Astronomy Observatory at 110 MHz. The Chilescope observatory detected an optical transient of ∼ 19 m on the third day in the outskirts of the galaxy NGC 4993; we continued observations following its rapid decrease. We put an upper limit of 1.5 × 10 4 Jy on any radio source with a duration of 10-60 s which may be assoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
105
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(115 citation statements)
references
References 107 publications
10
105
0
Order By: Relevance
“…It makes the problem of correct blind classification still very actual, especially in the new era of gravitational wave astronomy. The one and only confirmed gamma-ray burst for the moment, associated with gravitational waves, GRB 170817, is placed in the middle of the overlap region (Abbott et al 2017a,b;Goldstein et al 2017;Pozanenko et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It makes the problem of correct blind classification still very actual, especially in the new era of gravitational wave astronomy. The one and only confirmed gamma-ray burst for the moment, associated with gravitational waves, GRB 170817, is placed in the middle of the overlap region (Abbott et al 2017a,b;Goldstein et al 2017;Pozanenko et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One more evident criterion can be added, the detection of kilonova emission for type I bursts (e.g. Jin et al 2016;Yang et al 2015;Tanaka 2016;Pozanenko et al 2018;Pandey et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…From the residual, we noticed that a peaked component should be added to improve the fit. For this reason we refit the spectrum Pozanenko et al 2015) and the fit of the composite XRT-BAT-GBM spectrum (red solid line). The grey shaded area represents the 1σ scatter from the best fit.…”
Section: Xmm-newton Late Time Spectrummentioning
confidence: 99%
“…The first component is a short hard spike whose spectrum can be fit by a CPL with peak energy Ep = 230 +310 −80 keV. The preferred fit for the spectrum of the second component is a blackbody model with kT = 11.3 +3.8 −2.4 keV (Goldstein et al 2017;Zhang et al 2018), but a nonthermal origin with a CPL model fit of Ep = 43 +9 −7 keV cannot be ruled out (Zhang et al 2018;Pozanenko et al 2018). In this section, we compare the properties of GRB 170817A to the short GRBs with EE in our sample.…”
Section: Grb 170817a In Comparison To Short Grbs With Eementioning
confidence: 99%
“…More interestingly, the short GRB 170817A associated with the gravitational wave event (GW 170817) from double a NS merger was recently detected by Fermi/GBM (Abbott et al 2017;Goldstein et al 2017), and was found to have a prompt emission that is composed of a hard spike of 0.8 s and a weak tail of up to 2.3 s (Goldstein et al 2017;Zhang et al 2018;Pozanenko et al 2018). An interesting question is whether or not GRB 170817A differs in its spectral properties from other typical short GRBs with EE.…”
Section: Introductionmentioning
confidence: 99%